LEGISLAÇÃO AMBIENTAL PORTUÁRIA PARA SUA GESTÃO: Estudo de Caso do Porto de Porto Alegre - RS - Leite, Denise dos Santos (2012)
Brazilian environmental legislation is very wide, setting many times, difficult to service obligations by port activity. The objective of this dissertation is to identify and analyze key environmental laws applicable to the Brazilian port activity with regard to environmental licensing and mandatory environmental audits, and perform an analysis of port environmental management in the international community to identify strengths that can contribute to the Brazilian ports. The research methodology used was based on a review of the literature, consultation with environmental legislation and other regulatory frameworks, and field research in the port of Porto Alegre (RS) which was the subject of the case study .The results obtained show the status of compliance with environmental legislation and implementation of environmental management in Porto. The conclusion is that the port of Porto Alegre is in its infancy with regard to the implementation of environmental management, showing many points to be adopted to improve environmental management and meeting the applicable environmental laws. An improvement of great importance to be implemented is the effective implementation of a sector of Environment with trained professionals for the analysis of environmental legislation to port.